Analysis of Risk Factors Associated with Early Childhood Caries - Li RY; Yang DM; Ding N; Bao QY (Dove Medical Press, 2023)
Rong-Yin Li,1 Dong-Mei Yang,2 Nan Ding,1 Qi-Yan Bao1 1Department of Stomatology, Beijing Luhe Hospital, Capital Medical University, Beijing, 101149, People's Republic of China; 2Department of Pediatric Dentistry, Capital Medical University School of Stomatology, Beijing, 100050, People's Republic of ChinaCorrespondence: Dong-Mei Yang, Department of Pediatric Dentistry, Capital Medical University School of Stomatology, No. 4 Tiantan Xili, Dongcheng District, Beijing, 100050, People's Republic of China, Tel +86 10 57099201, Email yangdm1004@126.comObjective: To identify the main factors associated with early childhood caries by analyzing the risk factors of early childhood caries, thus providing a reference for developing prevention programs to reduce the risk of early childhood caries.Methods: We selected a total of 221 children aged 3- 4 years from two kindergartens in Tongzhou District, Beijing for this study. We conducted oral examination and the caries activity test (Cariostat) on children and their parents / primary caregivers, and the parents / primary caregivers additionally answered a questionnaire survey. Based on the results, we comprehensively evaluated the caries status of children and statistically analyzed the caries-related factors to identify the relevant risk factors.Results: The mean age of children in the study children was 40.08 ± 2.65 months, with a caries prevalence rate of 54.97% and a mean caries value of 4.61. Early childhood caries was correlated with the intake frequency of sugary foods, intake of sugary foods before bedtime, frequency of tooth brushing, oral health knowledge of parents, caries susceptibility, and age of starting to brush teeth. Logistic regression analysis results showed that the intake frequency of sugary foods, oral health knowledge of parents, and caries susceptibility were the factors influencing early childhood caries, especially the intake frequency of sugary foods.Conclusion: The intake frequency of sugary foods, intake of sugary foods before bedtime, frequency of brushing teeth, oral health knowledge of parents, caries susceptibility, and age of starting to brush teeth were associated with early childhood caries. Among these, the intake frequency of sugary foods, oral health knowledge of parents, and caries susceptibility, especially the intake frequency of sugary foods, were the influencing factors.Keywords: correlation analysis, early childhood caries, risk factor evaluation, susceptibility